2022
DOI: 10.1007/s00432-022-04112-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarker panel diagnostics in pancreatic ductal adenocarcinoma: the clinical utility of soluble interleukins, IFN-γ, TNF-α and PD-1/PD-L1 in comparison to established serum tumor markers

Abstract: Purpose Novel biomarkers to better predict outcome and select the best therapeutic strategy for the individual patient are necessary for pancreatic ductal adenocarcinoma (PDAC). Methods Using a panel assay, multiple biomarkers (IFN-γ, IL-10, IL-6, IL-8, TNF-α, CEA, CA 19–9, CYFRA 21–1, HE4, PD-1 and PD-L1 levels) were measured in serum samples of 162 patients with resected, locally advanced and metastatic PDAC in this retrospective single-center study. Opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Furthermore, we compared the group of 88 patients with synchronous metastatic disease to a historic cohort of 90 patients with pancreatic cancer with synchronous metastatic disease who had been diagnosed at our comprehensive cancer center between December 2010 and August 2017. The baseline characteristics of this group including also some patients with metachronous metastatic disease have been reported previously [ 18 ]. The proportion of male and female patients was similar in both cohorts (MTB cohort 63.3% male vs comparative cohort 65.9% male).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we compared the group of 88 patients with synchronous metastatic disease to a historic cohort of 90 patients with pancreatic cancer with synchronous metastatic disease who had been diagnosed at our comprehensive cancer center between December 2010 and August 2017. The baseline characteristics of this group including also some patients with metachronous metastatic disease have been reported previously [ 18 ]. The proportion of male and female patients was similar in both cohorts (MTB cohort 63.3% male vs comparative cohort 65.9% male).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, soluble checkpoints are also considered novel therapeutic targets and potential biomarkers. Indeed, high levels of both sPD-1 and sPD-L1 forms have been detected in plasma/serum of different cancer patients, compared to healthy donors (HDs), and have been associated with tumor prognosis, therapeutic response and overall survival (OS) (32)(33)(34)(35)(36)(37). Although, several studies demonstrated the pivotal role of sPD-1 in controlling cytotoxic T cells anti-cancer function, there is a lack of knowledge on the role of sPD-1 toward human NK cells.…”
Section: Introductionmentioning
confidence: 99%